PENGETAHUAN REMAJA TENTANG RESUSITASI JANTUNG PARU BERHUBUNGAN DENGAN EFIKASI DIRI REMAJA DI SMK NEGERI 2 SINGOSARI MALANG - Yasin, Dudella Desnani Firman; Ahsan, Ahsan; Racmawati, Septi Dewi (Universitas Tribhuwana Tunggadewi, 2020)
The focus of current global health problems is the death rate that occurs outside the Hospital Out-of-Hospital Cardiac Arrest (OHCA) due to cardiac arrest. Every year the incidence rate is very high and increasing. Delay in reporting and providing Lung Resuscitation can result in death. Providing knowledge about CPR is expected to reduce mortality due to cardiac arrest. The purpose of this study was to determine the relationship of knowledge with adolescent self-efficacy in performing Pulmonary Resuscitation. The research design used was cross-sectional study. The research location is SMK Negeri 2 Singosari Malang. The number of respondents was 110 respondents taken by purposive sampling technique. Data analysis using chi-square test that is knowledge obtained p = 0.003 (p